2012
DOI: 10.4067/s0718-915x2012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Mapa de corrosión atmosférica de Chile: resultados después de un año de exposición

Abstract: Palabras clave: Corrosión atmosférica, mapa de corrosión de Chile, acero al carbono, acero galvanizado, cobre y aluminio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The present study is part of the construction of a map of atmospheric corrosion in Chile and the aim is to present the results obtained for the behaviour of copper against atmospheric corrosion at seven sites in the fifth region of Chile: Quintero, Valparaíso, Curauma, Casablanca, Quilpué, Los Andes and Río Blanco.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is part of the construction of a map of atmospheric corrosion in Chile and the aim is to present the results obtained for the behaviour of copper against atmospheric corrosion at seven sites in the fifth region of Chile: Quintero, Valparaíso, Curauma, Casablanca, Quilpué, Los Andes and Río Blanco.…”
Section: Introductionmentioning
confidence: 99%
“…To best establish steel behaviors in aggressive environments, Figure 3 presents variations in corrosion rate and corrosion loss, where steel corrosion rates from the four study stations are presented in Figure 3 a. It can be observed that, as exposure time increases, the corrosion rate is reduced; this is attributed to the fact that as corrosion forms, it creates a protective layer [ 15 ]. This behavior follows an exponential curve, except at the Quintero station—this site had the greatest corrosion rate, and with the mix of industrial–marine environments, had an inconsistent behavior, based on the variations of these environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…SAE 1020 steel coupons (100 mm × 100 mm × 4 mm) were used as probes, placed at 45° angles and separated by plastic isolators. These were installed according to ISO standards 9223 to 9226 [ 21 , 22 , 23 , 24 ] at different locations in Chile, for 36 months, beginning in March 2010 [ 14 , 15 ]. The metals’ chemical compositions were analyzed by X-ray spectrometry, and are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuing this line of research on atmospheric corrosion behavior and corrosion effects on material toughness, and framed in contributing to a complete atmospheric corrosion map of Chile, this report presents toughness results over 3 years of exposure for carbon steel and galvanized steel at seven sites across the Fifth Region of Chile: Quintero, Valparaíso, Curauma, Casablanca, Quilpué, Los Andes, and Río Blanco. The study also contributes by providing applications of predictive models for the mechanical properties measured in relation to the corrosion rate.…”
Section: Introductionmentioning
confidence: 99%